THE ROLE OF NATIONAL INTEREST AS THE DRIVING AND OBSTRUCTING FACTOR IN THE INTERNATIONAL COMMITMENT VIEWED BY MORGENTHAUâS THEORIES OF INTERNATIONAL RELATIONS. - Santoso, Mohamad Imam (Jurnal Ilmiah Administrasi Publik, 2013)
Abstract: The Role of National Interest as the Driving and Obstructing Factor in the International Commitment viewed by Morgenthauâs Theories ofÂ  International Relations. International commitment needs every party states to comply with the international treaty or convention. However, while the agreements and treaties already constructed, the implementation of these decision are much more difficult to implemented.Â  Hans Morgenthau presents his theory about the national interests while implemented in the international relations. In his realism approach, there is no powerful country can make the international relations based on their idea and they must respect the others. Such cases of national policy and ideology defended by country therefore ignore the counterparts requirement. Finally, the national interest is likely weaken the consensus rather than to make it closer cooperation. Keywords: Agreements and Treaties, International Law, National Interest. Abstrak: Peran Kepentingan Nasional sebagai Faktor Pengendali dan Penghalang dalam Komitmen Internasional dilihat oleh Teori Morgenthau tentang Hubungan Internasional. Perjanjian internasional mewajibkan komitmen bagi setiap negara peserta. Tetapi, jika perjanjian itu disepakati, penerapannya masih memerlukan negosiasi. Kepentingan nasional para pihak seringkali mengabaikan peserta lain dan pertimbangan kepentingan nasional ini umumnya mempersulit terjadinya kesepakatan bersama. Â  Kata Kunci: perjanjian, hukum internasional dan kepentingan nasional.